2013
DOI: 10.1158/0008-5472.can-12-3920
|View full text |Cite
|
Sign up to set email alerts
|

scFv-Based “Grababody” as a General Strategy to Improve Recruitment of Immune Effector Cells to Antibody-Targeted Tumors

Abstract: Recruitment of immune cells to tumor cells targeted by a therapeutic antibody can heighten the antitumor efficacy of the antibody. For example, p185her2/neu-targeting antibodies not only downregulate the p185her2/neu kinase (ERBB2) but also trigger complement-dependent cytotoxicity (CDC) and antibody-dependent cellular cytotoxicity (ADCC) through the antibody Fc region. Here we describe a generalized strategy to improve immune cell recruitment to targeted cancer cells, using a modified scFv antibody we call a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…One of the monoclonal antibodies, mAb7.16.4, has a shared epitope with trastuzumab, a FDA approved therapeutic agent in clinical use (Zhang et al, 1999). 7.16.4 is active on Erbb2/neu transformed rodent and human tumors in a variety of assays (Cai et al, 2013; Zhang et al, 1999). 7.16.4 has been used in many labs around the world in transgenic animal models of tumors induced by the neu oncogene (Katsumata et al, 1995; Park et al, 2010; Stagg et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…One of the monoclonal antibodies, mAb7.16.4, has a shared epitope with trastuzumab, a FDA approved therapeutic agent in clinical use (Zhang et al, 1999). 7.16.4 is active on Erbb2/neu transformed rodent and human tumors in a variety of assays (Cai et al, 2013; Zhang et al, 1999). 7.16.4 has been used in many labs around the world in transgenic animal models of tumors induced by the neu oncogene (Katsumata et al, 1995; Park et al, 2010; Stagg et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The association constant, dissociation constant and affinity of the complexes consisting of anti-HER2 scFv and recombinant extracellular domain of the HER2 receptor p185 HER2-ECD (Sino Biological, Inc., Beijing, China) were determined by BIAcoreX100 (GE Healthcare) bio-molecular interaction analyzer based on surface plasmon resonance. 49 …”
Section: Methodsmentioning
confidence: 99%
“…Another way to potentially enhance the antitumor efficacy of HER2-targeted mAbs is through the modification of the HER2 single-chain variable fragment (scFv) domain, which binds a target protein other than HER2 30 . Greene et al reported the results of a breast cancer xenograft model, demonstrating the antitumor efficacy of a HER2 scFv and an IFN-γ engineered protein 31 .…”
Section: Her2-directed Mabsmentioning
confidence: 99%